Bone Mass in Anorexia Nervosa and Thin Postmenopausal Women-Related Secondary Amenorrhea - Mascarenhas, Mário Rui; Barbosa, Ana Paula; Jorge, Zulmira; Nobre, Ema; Gonçalves, Ana; Oliveira, António Gouveia de; Carmo, Isabel do (IntechOpen, 2011)
None